2023
DOI: 10.1177/03946320231178769
|View full text |Cite
|
Sign up to set email alerts
|

Systemic inflammation factors as survival prognosis markers in ovarian neoplasm and the relationship with cancer-associated inflammatory mediators—a review

Abstract: At the level of the genital system, ovarian neoplasm is the most frequent cause of morbidity and mortality. In the specialized literature, the coexistence of an inflammatory process is admitted from the early stages of the evolution of this pathology. Starting from the importance of this process, both in determinism and in the evolution of carcinogenesis and summarizing the field of knowledge, for this study we considered two objectives: the first was the presentation of the pathogenic mechanism, through which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 106 publications
(188 reference statements)
0
1
0
Order By: Relevance
“…Increasing evidence suggested that systemic inflammatory biomarkers were valid predictors of prognosis in multiple cancers. [2][3][4][5] Blood inflammation parameters such as neutrophil-to-lymphocyte ratio (NLR), lymphocyte-to-monocyte ratio (LMR), neutrophil-to-platelet ratio (NPR), platelet-to-lymphocyte ratio (PLR), monocyte-to-lymphocyte ratio (MLR) and index of systemic immune-inflammation (SII) have been associated with the prognosis of cervical cancer. [6][7][8] Computed tomography (CT) -derived body composition measures have been widely studied as important prognostic markers in patients with cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Increasing evidence suggested that systemic inflammatory biomarkers were valid predictors of prognosis in multiple cancers. [2][3][4][5] Blood inflammation parameters such as neutrophil-to-lymphocyte ratio (NLR), lymphocyte-to-monocyte ratio (LMR), neutrophil-to-platelet ratio (NPR), platelet-to-lymphocyte ratio (PLR), monocyte-to-lymphocyte ratio (MLR) and index of systemic immune-inflammation (SII) have been associated with the prognosis of cervical cancer. [6][7][8] Computed tomography (CT) -derived body composition measures have been widely studied as important prognostic markers in patients with cancer.…”
Section: Introductionmentioning
confidence: 99%